Electrolysis Cell Learning Media Based on Virtual Reality Millealab - Indah Langitasari; Isriyanti Affifah; Ratna Sari Siti Aisyah; Muhammad Alfian Pratama (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
The electrolytic cell is a chemical material with abstract and concrete concept characteristics. Students often need help learning this material, especially connecting concrete and abstract concepts. Therefore, media is needed that can facilitate students in understanding electrolytic cell material, which is made interesting by utilizing virtual reality technology. The purpose of this research is to produce chemistry learning media based on virtual reality with a feasible and practical MilleaLab platform. The research uses the ADDIE development model (analysis, design, develop, implement, evaluate). The product of this research is virtual reality-based learning media on the MilleaLab platform. The validation assessment from media and material experts with an error rate of 5% based on the Aiken scale obtained Vcount ≥ Vtable (Vtable = 0.87). Each value in the validation of media and material experts is 0.89 and 0.87 with the Valid category. The results of assessing student responses regarding the practicality of this learning media get 88% in the Very Good category. Based on these results, it can be concluded that MilleaLab virtual reality-based learning media on electrolytic cell material is a learning medium that is practical and feasible to use.